2001
DOI: 10.1046/j.1525-1438.2001.01013.x
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite instability in uterine sarcomas

Abstract: Studies have shown a 15-30% frequency of microsatellite instability in endometrial cancer. In addition, we found a 21% frequency of microsatellite instability in endometrial cancer. Our aim was to investigate the presence of microsatellite instability and loss of heterozygosity in uterine sarcomas. The records of 69 women referred to Kalafong Academic and Pretoria Academic Hospital with a primary diagnosis of uterine sarcoma were reviewed. At histological review of 43 cases with a primary diagnosis of leiomyos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 26 publications
2
19
1
Order By: Relevance
“…Although MSI has been reported to be infrequent in uterine carcinosarcomas (B5%), 12,13 recent studies from our laboratory have suggested that MSI may be more common in uterine carcinosarcomas than previously described and that defective DNA mismatch repair may be a feature unique to the epithelial component of these tumors. [12][13][14] We therefore sought to determine the DNA mismatch repair and TP53 status in each component of uterine carcinosarcomas in an attempt to better understand the histiogenesis of these malignancies.…”
mentioning
confidence: 62%
“…Although MSI has been reported to be infrequent in uterine carcinosarcomas (B5%), 12,13 recent studies from our laboratory have suggested that MSI may be more common in uterine carcinosarcomas than previously described and that defective DNA mismatch repair may be a feature unique to the epithelial component of these tumors. [12][13][14] We therefore sought to determine the DNA mismatch repair and TP53 status in each component of uterine carcinosarcomas in an attempt to better understand the histiogenesis of these malignancies.…”
mentioning
confidence: 62%
“…2,32,33 Microsatellite instability is caused by an inability of the MMR system to cut out and replace the mismatching DNA strains due to methylation or mutation of its proteins (MLH1, MSH2 and MSH6). 34 Two previous studies showed that microsatellite instability was present in 5% 35 and 23.3% 21 of uterine carcinosarcomas. The latter study observed that microsatellite instability is mainly a feature of the epithelial component.…”
Section: Discussionmentioning
confidence: 99%
“…The same tumors were investigated also for LOH but the results were then less clear-cut. Amant et al (2001) found no LOH in the five tumors they examined. Moinfar et al (2004) studied a total of 27 tumors (20 ESS, four ESN, and three UES) as well as samples of non-tumorous surrounding tissue.…”
Section: Microsatellite Instability (Msi) and Loss Of Heterozygosity mentioning
confidence: 85%